A carbon fiber electromagnetic shielding composite material based on a multi-scale gradient impedance matching network and a preparation method thereof
Patent Information
- Application Number
- CN202611194000.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-07
- Publication Date
- 2026-10-30
AI Technical Summary
[0006]参见公开号为CN120248529A的专利公开了一种高性能宽波段电磁屏蔽碳纤维预浸料,其将MXene纳米片与水性聚合物树脂复合,实现了宽波段屏蔽,但MXene仅以简单混合方式分散于树脂中,未实现与碳纤维表面的有序锚固,未构建梯度阻抗结构
1、通过设计三层梯度阻抗匹配网络结构,使入射电磁波在阻抗匹配层表面产生较低的初始反射率(反射系数Γ<0.2),电磁波逐步进入材料内部后,在损耗吸收层中通过介电损耗、磁损耗和导电损耗的多机制协同作用被高效吸收;
Smart Images

Figure CN123021633A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of composite materials technology, specifically to electromagnetic shielding polymer composite materials, and particularly to a carbon fiber electromagnetic shielding composite material based on a multi-scale gradient impedance matching network and its preparation method. Background Technology
[0002] With the rapid development of 5G / 6G communication technology, high-power electronic devices, and aerospace equipment, electromagnetic interference (EMI) and electromagnetic pollution are becoming increasingly serious problems. Electromagnetic waves not only severely interfere with the normal operation of precision electronic equipment but also pose potential hazards to human health. Therefore, the development of high-performance electromagnetic shielding materials has become a research hotspot in the fields of materials science and electronic engineering.
[0003] Carbon fiber (CF) is considered an ideal reinforcement for preparing lightweight electromagnetic shielding composite materials due to its excellent specific strength, specific modulus, high temperature resistance, and intrinsic conductivity. By introducing carbon fibers and their derivative fillers into the polymer matrix, a conductive network can be constructed to achieve electromagnetic shielding function. However, existing carbon fiber-based electromagnetic shielding materials still face many technical bottlenecks in terms of structural design, filler synergy, and preparation process, which limit their practical application effectiveness.
[0004] See the patent with publication number CN205223076U, which discloses a nickel-plated carbon fiber plate with electromagnetic shielding performance. It uses carbon fiber cloth as the substrate and adopts a three-layer coating structure design of magnetron sputtering nickel plating, copper electroplating, and nickel electroplating. The electromagnetic shielding effectiveness is greater than 40dB in the 150kHz~18GHz frequency band. However, this material is mainly based on the reflection mechanism, mainly relying on the high conductivity of the metal coating to reflect electromagnetic waves. The absorption ratio is low, and the bonding between the coating and the carbon fiber interface mainly relies on physical adsorption. The coating is prone to peeling off during long-term use.
[0005] See the patent with publication number CN117801465A, which discloses a modified carbon fiber electromagnetic shielding composite material. It introduces ZnO and carbonyl iron powder magnetic particles to improve electromagnetic wave absorption through the synergistic effect of dielectric loss and magnetic loss. Although magnetic fillers are introduced to enhance absorption, the bonding strength between the metal coating and the carbon fiber matrix is still limited, and two-dimensional nanomaterials such as MXene are not used for interface bridging. The efficiency of conductive network construction needs to be improved.
[0006] See the patent with publication number CN120248529A, which discloses a high-performance broadband electromagnetic shielding carbon fiber prepreg. It combines MXene nanosheets with water-based polymer resin to achieve broadband shielding. However, MXene is only dispersed in the resin in a simple mixing manner and does not achieve orderly anchoring with the carbon fiber surface, and does not build a gradient impedance structure. Summary of the Invention
[0007] One objective of this invention is to provide a carbon fiber electromagnetic shielding composite material that achieves a gradient functional design from impedance matching to loss absorption through a multi-scale gradient impedance matching network structure, thereby realizing the synergistic effect of multiple mechanisms of dielectric loss, magnetic loss and conductive loss, and achieving high shielding effectiveness and high absorption ratio over a wide frequency range.
[0008] To achieve the above objectives, the technical solution adopted by the present invention is as follows: A carbon fiber electromagnetic shielding composite material includes an impedance matching layer, a loss absorption layer, and a reflective underlayer sequentially distributed along the thickness direction, wherein transition interface regions are provided between the impedance matching layer and the loss absorption layer, and between the loss absorption layer and the reflective underlayer. The impedance matching layer, loss absorption layer, and reflective underlayer all contain a matrix material and functional fillers distributed within the matrix material. The functional fillers include nickel-plated carbon fibers, MXene nanosheets, and Fe3O4@SiO2 particles. The MXene nanosheets coat the surface of the nickel-plated carbon fibers and form a conductive framework that penetrates the impedance matching layer, loss absorption layer, and reflective underlayer. The Fe3O4@SiO2 particles are dispersed in the three-dimensional network gaps of the conductive framework. The total content of functional fillers in the loss absorption layer is higher than that in the impedance matching layer, and the content of nickel-plated carbon fibers in the reflective underlayer is higher than that in the loss absorption layer.
[0009] In this invention, the "dispersed distribution" of Fe3O4@SiO2 particles has fundamental differences and technical advantages over the simple "embedding" in existing technologies. First: Different spatial positioning accuracy: The diffuse distribution ensures that Fe3O4@SiO2 particles are precisely distributed in the gaps of the three-dimensional conductive network constructed by Ni-CF / MXene, rather than being randomly dispersed in the matrix resin, thus ensuring the spatial coordination of magnetic loss units and dielectric loss units. Second: Different interface coupling effects: Dispersed distribution causes Fe3O4@SiO2 particles to form a large number of heterogeneous interfaces with the conductive framework surface, resulting in strong interface polarization loss, while the embedded method lacks this ordered interface coupling. Third: Different permeation threshold control: Dispersed distribution can form an effective magnetic loss path at a lower filler content (2-8wt%), while the embedded method requires a higher content to achieve the same effect; Fourth: The continuity of impedance gradient is different: the diffuse distribution combined with the gradient structure can achieve a continuous and gradual change in dielectric constant and permeability, while the embedded method is difficult to achieve such precise control.
[0010] The beneficial effects of the above-mentioned diffuse distribution are achieved through the following mechanism: the SiO2 shell of Fe3O4@SiO2 particles has a low dielectric constant, forming a dielectric "island" effect in the gaps of the Ni-CF / MXene high dielectric network. This avoids the excessively high dielectric constant caused by direct contact of conductive fillers, and also achieves local impedance matching optimization through shell thickness control.
[0011] The cross-scale cascade distribution of the three types of fillers forms a full-scale electromagnetic response network from millimeters to nanometers, improving the response capability to electromagnetic waves of different wavelengths over a wide frequency range.
[0012] Preferably, in the above technical solution, the total content of the functional filler is 7.5~47wt%, wherein: the content of the nickel-plated carbon fiber is 16~32wt%, the content of the MXene nanosheets is 0.3~6wt%, and the content of the Fe3O4@SiO2 particles is 1.2~9wt%. The functional filler forms conductive networks ranging from quasi-continuous to fully continuous in the three layers. The percolation threshold of the nickel-plated carbon fiber is approximately 8-12wt%. The MXene nanosheets are auxiliary fillers; excessive amounts will lead to excessively high dielectric constants and deteriorate impedance matching. The Fe3O4@SiO2 provides moderate magnetic loss; excessive amounts will increase density and cause magnetic loss to tend to saturate.
[0013] Preferably, in the impedance matching layer, the total content of the functional filler is 7.5~25wt%, wherein the content of the nickel-plated carbon fiber is 6~18wt%, the content of the MXene nanosheets is 0.3~2wt%, and the content of the Fe3O4@SiO2 particles is 1.2~5wt%.
[0014] Preferably, in the above technical solution, the total content of the functional filler in the loss absorption layer is 12.5~38wt%, wherein the content of the nickel-plated carbon fiber is 10~25wt%, the content of the MXene nanosheets is 0.5~5wt%, and the content of the Fe3O4@SiO2 particles is 2~5wt%.
[0015] Preferably, in the above technical solution, the total content of the functional filler in the reflective substrate is 17.5~47wt%, wherein the content of the nickel-plated carbon fiber is 14~32wt%, the content of the MXene nanosheets is 0.7~6wt%, and the content of the Fe3O4@SiO2 particles is 2.8~9wt%.
[0016] In the preferred embodiment of the above technical solution, the total thickness of the composite material is 1~5mm, which balances the requirements of shielding effectiveness and lightweight design.
[0017] Preferably, in the above technical solution, the thickness ratio of the impedance matching layer, the loss absorption layer, and the reflective underlayer is (2~4):(3~6):(1~3). The impedance matching layer realizes a gradual impedance transition, the loss absorption layer is the main site for electromagnetic energy dissipation, and the reflective underlayer mainly plays a reflection role rather than absorption.
[0018] Preferably, the thickness of the transition interface region is 30~150μm. Based on the diffusion distance of the filler concentration gradient and the skin depth of the electromagnetic wave at the interface, the transition interface region that is too thin cannot effectively eliminate the interface discontinuity effect, while that that is too thick will blur the three functional partitions.
[0019] More preferably, in the transition interface region, the spatial density of the conductive skeleton gradually changes from the impedance matching layer to the reflective sublayer, rather than being abruptly interrupted.
[0020] More preferably, the thickness of the transition interface region is 30-120 μm.
[0021] Preferably, in the above technical solution, the composite material from the impedance matching layer to the reflective bottom layer has a gradually increasing dielectric constant, a gradually increasing magnetic permeability, and a gradually increasing electrical conductivity.
[0022] Preferably, in the above technical solution, the relative permittivity of the impedance matching layer is 5~20, ensuring good impedance matching between the impedance matching layer and free space (air, wave impedance Z0≈377Ω), enabling electromagnetic waves to efficiently enter the material interior rather than be reflected by the surface; its nickel-plated carbon fiber content is the lowest among the three layers, and the dielectric constant is controlled at a low level by reducing the content of conductive filler; its MXene nanosheets are uniformly distributed in the impedance matching layer in a single-layer or few-layer dispersion state, ensuring that the two-dimensional structural characteristics of the MXene nanosheets are preserved, maximizing its specific surface area and interfacial polarization effect, while avoiding excessively high local dielectric constants due to agglomeration.
[0023] The permeability of the impedance matching layer is close to 1, and it is mainly dielectric matching rather than absorption.
[0024] Preferably, in the above technical solution, the relative permittivity of the loss absorption layer is 10~35, indicating that the layer has a stronger dielectric response capability, can support greater dielectric loss, and ensures effective polarization relaxation loss in the 8.2-40GHz frequency band.
[0025] The permeability of the loss absorption layer is 1.5-6, providing moderate magnetic loss, which effectively attenuates both the electric and magnetic field components of electromagnetic waves. The natural resonance frequency of magnetic Fe3O4 in the microwave band is approximately 1-2 GHz. Through nanoscale effects and shape anisotropy, the effective magnetic loss can be extended to the X-band and Ku-band. The permeability is 1.5-6; its nickel-plated carbon fibers, MXene nanosheets, and Fe3O4@SiO2 particles form a multi-scale synergistic loss network in the loss absorption layer. The nickel-plated carbon fibers provide conductive and leakage current losses, the MXene nanosheets provide interfacial polarization and dipole polarization losses, and the Fe3O4@SiO2 particles provide natural resonance, exchange resonance, and eddy current losses. The synergistic effect of these three loss mechanisms enables efficient conversion of electromagnetic energy.
[0026] Preferably, in the above technical solution, the conductivity of the reflective substrate is greater than 50 S / m. The high conductivity ensures that the layer has a strong reflective ability for electromagnetic waves, and can reflect almost all the residual electromagnetic waves that penetrate the loss absorption layer. The high conductivity of the filler is achieved by maximizing the content of conductive filler to form a continuous conductive network (the high conductivity state after the percolation network is fully established). The content of nickel-plated carbon fiber in the reflective substrate is the highest among the three layers, forming a continuous conductive network to reflect the penetrating electromagnetic waves. The formation of a continuous conductive network to reflect the penetrating electromagnetic waves clarifies the core functional positioning of the reflective substrate - not absorption, but reflection. The reflected electromagnetic waves undergo absorption and attenuation again in the loss absorption layer, which is equivalent to increasing the effective propagation path of the electromagnetic waves, thereby greatly improving the overall absorption efficiency.
[0027] Preferably, the matrix material of the above technical solution is selected from one or more of epoxy resin, polyimide, polyether ether ketone, polyphenylene sulfide, unsaturated polyester, phenolic resin and their modifiers, and has excellent mechanical properties, heat resistance and chemical stability.
[0028] Preferably, the composite material has an electromagnetic shielding effectiveness of 65-85dB in the 8.2-40GHz frequency band, an electromagnetic wave absorption rate of more than 80%, and a surface reflection coefficient of less than 5dB, making it suitable for electromagnetic shielding applications in aerospace vehicles, electronic equipment, or communication base stations.
[0029] One object of the present invention is to provide a method for preparing carbon fiber electromagnetic shielding composite material.
[0030] To achieve the above objectives, the technical solution adopted by the present invention is as follows: A method for preparing a carbon fiber electromagnetic shielding composite material, comprising: (1) Electroless nickel plating is performed on carbon fibers to obtain nickel-plated carbon fibers. (2) MXene nanosheets were electrostatically self-assembled onto the surface of nickel-plated carbon fiber to obtain nickel-plated carbon fiber-MXene composite filler. (3) Fe3O4@SiO2 nanoparticles were obtained by coating the surface of Fe3O4 with a SiO2 shell using an in-situ grafting method. (4) Nickel-plated carbon fiber-MXene composite filler and Fe3O4@SiO2 particles are combined with the matrix material in a gradient ratio to prepare an impedance matching layer, a loss absorption layer and a reflective underlayer. In each layer, the nickel-plated carbon fiber-MXene composite filler forms a conductive skeleton and Fe3O4@SiO2 particles are dispersed in the three-dimensional network gaps of the conductive skeleton. The impedance matching layer, loss absorption layer and reflective underlayer are laid in sequence. There is a preset filler concentration difference between adjacent layers of slurry. This concentration difference drives the filler to permeate and diffuse at the interlayer contact interface. Through vacuum-assisted impregnation, the resin matrix flows and drives Fe3O4@SiO2 to redistribute between layers. At the same time, the vacuum pressure makes each layer fit tightly but does not eliminate the established concentration gradient. After curing and shaping, the resin matrix gels and locks the formed concentration gradient into a stable transition interface region, and the composite material is obtained.
[0031] In this invention, the difference between "diffuse distribution" and general process methods is as follows: Conventional techniques typically employ mechanical stirring or ultrasonic dispersion to directly mix Fe3O4@SiO2 particles into the matrix resin, forming an "embedded" structure. This process has the following inherent drawbacks: the filler is randomly dispersed, making it impossible to guarantee the spatial coordination between the magnetic loss unit and the conductive framework; agglomeration is prone to occur at high filler contents, leading to abrupt changes in local dielectric constant and impedance mismatch; and there is a lack of ordered interface coupling, resulting in limited contribution to interface polarization loss.
[0032] This invention employs a "dispersion distribution" process, the core of which is: First, a Ni-CF / MXene three-dimensional conductive framework is constructed as a spatial template. Then, through a vacuum-assisted impregnation molding process, the matrix resin containing Fe3O4@SiO2 particles is fully penetrated into the gaps between the framework under vacuum. The nanoparticles automatically fill the gaps in the three-dimensional network with the resin flow, rather than being coated on the surface of the framework. This "build the framework first, then fill the gaps" preparation method achieves the following: Spatial order: Nanoparticles are precisely located in the gaps between conductive networks rather than being randomly distributed; Low content and high efficiency: An effective magnetic loss path can be formed at a low content, avoiding the high filling of more than 15wt% required by the embedding method; Interface synergy: Nanoparticles form a large number of heterogeneous interfaces with the surface of the conductive framework, resulting in strong interfacial polarization and dielectric-magnetic coupling loss. Gradient continuity: By controlling the concentration of nanoparticles in each layer of impregnation slurry, the magnetic permeability is continuously and gradually varied along the thickness direction.
[0033] Preferably, in the above technical solution, the length of the nickel-plated carbon fiber is 1-10mm, and the thickness of the nickel plating layer of the electroless nickel plating is 0.5-5μm, based on the balance between electromagnetic shielding effectiveness and interfacial bonding force: if it is too thin, the conductive network will be incomplete; if it is too thick, it will increase the weight and be easy to peel off. The length of the MXene nanosheets is 1-10 μm, and the MXene nanosheets are Ti3C2Tx. The MXene nanosheets have a coating rate of 60-90% on the surface of nickel-plated carbon fibers. They have excellent metallic conductivity and abundant surface functional groups, which ensures that they can completely coat nickel-plated carbon fibers with a diameter of about 7-14 μm (including a 0.5-5 μm nickel layer) while retaining the morphological advantages of two-dimensional nanosheets. The core-shell length of Fe3O4 in the Fe3O4@SiO2 particles is 50-500 nm, and the thickness of the SiO2 shell is 10-100 nm.
[0034] Preferably, in the electrostatic self-assembly of (2), the electrostatic voltage is 10-50V and the assembly time is 1-4h. In the in-situ grafting method in (3), a SiO2 shell layer is grown in situ on the Fe3O4 surface using a silane coupling agent as the grafting medium. The reaction temperature is 60-120℃ and the reaction time is 4-12h. In vacuum-assisted impregnation in (4): the vacuum degree is -0.08~-0.1MPa, the impregnation time is 2-6h, the curing temperature is 80-200℃, and the curing time is 2-4h.
[0035] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art: 1. By designing a three-layer gradient impedance matching network structure, the incident electromagnetic wave generates a low initial reflectivity (reflection coefficient Γ<0.2) on the surface of the impedance matching layer. After the electromagnetic wave gradually enters the interior of the material, it is efficiently absorbed in the loss absorption layer through the synergistic effect of multiple mechanisms such as dielectric loss, magnetic loss and conductive loss. 2. A three-level, multi-scale synergistic filler system is adopted: The first level, nickel-plated carbon fiber (length scale in mm), constructs the basic conductive framework, providing multiple reflection and scattering paths for electrical conductivity loss and electromagnetic waves; the second level, MXene nanosheets (length scale in μm) are coated on the carbon fiber surface to form a three-dimensional conductive network, providing abundant interfacial polarization loss and dipole polarization loss; the third level, Fe3O4@SiO2 particles (length scale in nm), provides magnetic loss mechanism and impedance matching control function. The spatially ordered distribution and functional synergy of the three fillers enable the composite material to simultaneously possess strong dielectric loss, magnetic loss and conductive loss capabilities, achieving efficient dissipation of electromagnetic energy.
[0036] 3. The synergistic effect of the multi-scale filler system and the broadband impedance matching design of the three-gradient structure enable the composite material to exhibit excellent electromagnetic shielding performance in both the X-band (8.2-12.4GHz) and the Ku-band (12.4-18GHz). Attached Figure Description
[0037] Appendix Figure 1 This is a schematic diagram of the overall structure of the composite material in this embodiment. Detailed Implementation
[0038] The technical solution of the present invention will now be clearly and completely described with reference to the accompanying drawings. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0039] like Figure 1 As shown, it illustrates the three-layer gradient impedance matching structure of the composite material and the spatial arrangement of the functional zones of each layer. An incident electromagnetic wave is incident from one side of the impedance matching layer. The propagation path of the electromagnetic wave demonstrates the multiple reflections and absorption processes of the electromagnetic wave in the gradient structure.
[0040] A carbon fiber electromagnetic shielding composite material includes an impedance matching layer, a loss absorption layer, and a reflective substrate distributed sequentially along the thickness direction. Transition interface regions are provided between the impedance matching layer and the loss absorption layer, and between the loss absorption layer and the reflective substrate. In use, the impedance matching layer, loss absorption layer, and reflective substrate are arranged sequentially along the electromagnetic wave incident direction. Based on the impedance matching-loss-reflection synergistic mechanism in electromagnetic wave propagation theory: the electromagnetic wave first enters the low-impedance impedance matching layer to reduce surface reflection, and is subsequently absorbed and converted by dielectric and magnetic loss materials in the loss absorption layer. The residual electromagnetic wave is reflected back to the loss absorption layer by the reflective substrate for secondary absorption. This differs from traditional single-layer uniform shielding materials and is the structural basis for achieving "high absorption" electromagnetic shielding.
[0041] The total thickness of the composite material is 1~5mm, balancing shielding effectiveness and lightweight requirements. Among them, the thickness ratio of the impedance matching layer, loss absorption layer and reflection bottom layer is (2~4):(3~6):(1~3), the thickness of the transition interface region is 30~150μm, and the thickness of the transition interface region is 30-120μm.
[0042] The impedance matching layer, loss absorption layer, and reflection underlayer all contain a matrix material and functional fillers distributed within the matrix material. Specifically: The matrix material is a thermosetting or high-performance thermoplastic polymer with excellent mechanical properties, heat resistance and chemical stability, selected from one or more of epoxy resin, polyimide, polyether ether ketone, polyphenylene sulfide, unsaturated polyester, phenolic resin and their modifiers.
[0043] The functional filler comprises nickel-plated carbon fiber (Ni-CF), MXene nanosheets, and Fe3O4@SiO2 particles. MXene nanosheets coat the surface of the nickel-plated carbon fiber and form a conductive framework that penetrates the impedance matching layer, loss absorption layer, and reflection layer. The spatial density of the conductive framework gradually transitions in each transition interface region, resulting in a continuous gradient change in dielectric constant, magnetic permeability, and electrical conductivity along the thickness direction of the composite material. Fe3O4@SiO2 particles are dispersed in the three-dimensional network gaps of the conductive framework. The nickel-plated carbon fiber forms a penetrating basic conductive framework in the three layers and provides conductive loss and multiple scattering paths for electromagnetic waves. The MXene nanosheets provide interfacial polarization loss and dipole polarization loss, while the Fe3O4@SiO2 particles provide magnetic loss and impedance matching modulation, exhibiting a cross-scale cascade distribution in space.
[0044] Millimeter-scale nickel-plated carbon fibers (1-10 mm in length) serve as the basic conductive framework. When their size is comparable to the microwave wavelength, they can generate multiple scattering effects and provide continuous conductive loss channels. Micrometer-scale MXene nanosheets (1-10 μm in length) are coated on the surface of nickel-plated carbon fibers to form a cascade structure. They utilize their abundant surface functional groups (-O, -OH, -F) and interlayer defects to generate interfacial polarization and dipole polarization losses. Nanoscale Fe3O4@SiO2 particles (50-500 nm) are dispersed in the gaps of the three-dimensional network, providing magnetic losses (natural resonance and exchange resonance) and optimizing impedance matching by modulating the dielectric constant through the SiO2 shell.
[0045] The total content of functional fillers in the loss absorption layer is higher than that in the impedance matching layer, and the content of nickel-plated carbon fiber in the reflective underlayer is higher than that in the loss absorption layer. This results in a spatial density gradient distribution of functional fillers in the three layers, and the composite material forms a gradient impedance matching network with gradually increasing dielectric constant, magnetic permeability, and electrical conductivity along the thickness direction.
[0046] In the impedance matching layer, the total content of functional fillers is 7.5~25wt%, of which: the content of nickel-plated carbon fiber is 6~18wt%, the content of MXene nanosheets is 0.3~2wt%, and the content of Fe3O4@SiO2 particles is 1.2~5wt%. The relative permittivity of the impedance matching layer is 5-20, and the magnetic permeability is close to 1. Its nickel-plated carbon fiber content is the lowest among the three layers. MXene nanosheets are uniformly distributed in the impedance matching layer in a single layer or a few layers.
[0047] In the loss absorption layer, the total content of functional fillers is 12.5~38wt%, of which: the content of nickel-plated carbon fiber is 10~25wt%, the content of MXene nanosheets is 0.5~5wt%, and the content of Fe3O4@SiO2 particles is 2~5wt%. The relative permittivity of the loss absorption layer is 10⁻³⁵, and the magnetic permeability is 1.5-6. The nickel-plated carbon fiber, MXene nanosheets, and Fe3O4@SiO2 particles form a multi-scale synergistic loss network in the loss absorption layer.
[0048] In the reflective substrate, the total content of functional fillers is 17.5~47wt%, of which: the content of nickel-plated carbon fiber is 14~32wt%, the content of MXene nanosheets is 0.7~6wt%, and the content of Fe3O4@SiO2 particles is 2.8~9wt%. The conductivity of the reflective substrate is greater than 50 S / m, and its nickel-plated carbon fiber content is the highest among the three layers, forming a continuous conductive network to reflect penetrating electromagnetic waves.
[0049] The transition interface region avoids strong reflection and standing wave effects of electromagnetic waves at the interface caused by abrupt changes in filler density between the impedance matching layer, loss absorption layer and reflection bottom layer. The transition interface region achieves continuous impedance change through filler gradient transition, which conforms to the theory of gradual impedance transmission of electromagnetic waves in multi-layered media and improves broadband absorption performance.
[0050] The preparation method of this embodiment is described in detail below: The raw materials used in each embodiment and comparative example are as follows: [Matrix Material] A1: Epoxy resin (EP), Sinopec (Baling Petrochemical) produced E-51 bisphenol A type epoxy resin, epoxy value 0.51eq / 100g; A2: Polyimide (PI), DuPont Vespel SP-1; A3: Polyetheretherketone (PEEK), Victrex type PEEK resin produced by Zhongyan Polymer.
[0051] Nickel-plated carbon fiber B: T300 grade carbon fiber (Weihai Guangwei TZ300-12K, 12K specification, single filament diameter 7um), chemically nickel-plated, with a nickel layer thickness of 0.5-5um.
[0052] MXene Nanosheets C: Beijing FOSMAN Technology produces FMX-Ti3C2Tx single-layer nanosheets with a sheet size of 1-10um and a thickness of approximately 1-3nm.
[0053]
Fe3O4@SiO2 particles
[0054] Chemical Nickel Plating Solution E1: Nickel sulfate hexahydrate 25g / L; E2: Sodium hypophosphite 30g / L; E3: Sodium citrate 15g / L; E4: Ammonium chloride 30g / L; E5: Adjust the pH to 8.5-9.0 with ammonia.
[0055]
SiO2-coated raw materials
[0056] Curing agents and additives G1: Low molecular weight polyamide curing agent; G2: Acetone (for cleaning carbon fiber); G3: Deionized water.
[0057] Table 1: According to the formulation described in Table 1, Example 1 uses epoxy resin A1 as the matrix, with an impedance matching layer:loss absorption layer:reflection substrate ratio of 3:4:2, a total composite material thickness of 3 mm, and a transition interface region thickness of 80 μm. The preparation steps of Example 1 are as follows: (1) Take T300 grade carbon fiber bundle (Weihai Guangwei, brand TZ300-12K, 12K specification, single filament diameter about 7um), place it in acetone for reflux cleaning for 2h to remove the surface sizing agent, wash with deionized water and vacuum dry at 80 ℃ for 4h, immerse the pretreated carbon fiber in chemical nickel plating solution (prepared by E1-E5), control the temperature of the plating solution at 85±2 ℃, adjust the plating time in the range of 5-50min according to the target nickel layer thickness (corresponding to nickel layer thickness of 0.5-5um), control the plating time to 25min, and form a uniform nickel plating layer with a thickness of 2.5um (intermediate value) on the carbon fiber surface to obtain nickel-plated carbon fiber B; (2) MXene nanosheets C (sheet size 5um) were dispersed in deionized water to prepare a 2mg / mL dispersion. Nickel-plated carbon fiber B was placed in the dispersion and electrostatically self-assembled for 2.5h under an electrostatic voltage of 30V (intermediate value). The MXene coating rate was about 75% (intermediate value), and nickel-plated carbon fiber-MXene composite filler was obtained. (3) Preparation of Fe3O4 nanoparticles by coprecipitation method: FeCl3·6H2O and FeCl2·4H2O were dissolved in deionized water at a molar ratio of 2:1. Under nitrogen protection, concentrated ammonia was added to adjust the pH to 10-11, and the reaction was carried out at 80℃ for 1 hour. After magnetic separation and washing, Fe3O4 nanoparticles with a particle size of about 200 nm were obtained. Subsequently, a SiO2 shell was coated. The above Fe3O4 nanoparticles were dispersed in an ethanol-water mixture, and tetraethyl orthosilicate (TEOS) and ammonia catalyst were added. The mixture was stirred at room temperature for 4 hours to grow a SiO2 shell layer with a thickness of about 40 nm on the surface of Fe3O4 in situ, thus obtaining core-shell structured Fe3O4@SiO2 magnetic nanoparticles. Subsequently, 1.5 wt% coupling agent KH-550 was added, and the in-situ grafting reaction was carried out at 85℃ for 8 hours to introduce active amino functional groups on the surface of the SiO2 shell layer. After washing and drying, the nanoparticles were ready for use. The SiO2 coating reaction temperature was controlled at 80℃. Fe3O4@SiO2 core-shell nanoparticles D with a core-shell size of 200 nm and a SiO2 shell thickness of 40 nm were prepared by reacting at ℃ for 6 h.
[0058] (4) Using epoxy resin A1 as the matrix resin, prepare three-layer slurries according to the formula in Table 1. Impedance matching layer: 12wt% nickel-plated carbon fiber-MXene composite filler (approximately 11wt% Ni-CF + approximately 1wt% MXene), 3wt% Fe3O4@SiO2 particles, total filler 15wt%; Loss absorption layer: 18wt% nickel-plated carbon fiber-MXene composite filler (approximately 16wt% Ni-CF + approximately 2wt% MXene), 5wt% FFe3O4@SiO2 particles, total filler 23wt%; Reflective substrate: 24wt% nickel-plated carbon fiber-MXene composite filler (approx. 21wt% Ni-CF + approx. 3wt% MXene), 6wt% Fe3O4@SiO2 particles, total filler 30wt%. Impedance matching layer, loss absorption layer, and reflective underlayer preform are sequentially laid in a mold. During laying, the viscosity of the slurry between adjacent layers is controlled to be 800-1500 mPa•s. After laying, the layers are allowed to stand at room temperature for 10-20 minutes to allow limited mutual penetration and diffusion between adjacent layers due to the filler concentration difference, forming a transition interface region with a thickness of about 80 μm. Subsequently, vacuum-assisted impregnation is performed at a vacuum degree of -0.09 MPa for 4 hours. During the impregnation process, the resin flow drives the nano-sized particles to further redistribute between layers. At the same time, the vacuum pressure ensures that the layers are tightly bonded but does not eliminate the established concentration gradient. Finally, the layers are cured at 150 ℃ for 3 hours. During the curing process, the resin gelation locks the established concentration gradient into a stable transition interface region, resulting in a high-absorption carbon fiber electromagnetic shielding composite material with a three-layer gradient structure.
[0059] According to the formulation described in Table 1, the preparation method of Example 2 is basically the same as that of Example 1, except that: the thickness ratio of the three layers is 4:6:3, the total thickness of the composite material is 5 mm, the thickness of the transition interface region is 120 μm, and the other process parameters are the same as those of Example 1.
[0060] According to the formulation described in Table 1, the preparation method of Example 3 is basically the same as that of Example 1, except that: the thickness ratio of the three layers is 2:3:1, the total thickness of the composite material is 1 mm, the thickness of the transition interface region is 40 μm, and the other process parameters are the same as those of Example 1.
[0061] According to the formulation described in Table 1, the preparation method of Example 4 is basically the same as that of Example 1, except that: impedance matching layer: Ni-CF 18wt%, MXene 2.0wt%, Fe3O4@SiO2 5.0wt%, total filler 25wt%; loss absorption layer: Ni-CF 25wt%, MXene 5.0wt%, Fe3O4@SiO2 8.0wt%, total filler 38wt%; reflection underlayer: Ni-CF 32wt%, MXene 6.0wt%, Fe3O4@SiO2 9.0wt%, total filler 47wt%, and other process parameters are the same as in Example 1.
[0062] According to the formulation described in Table 1, the preparation method of Example 5 is basically the same as that of Example 1, except that: impedance matching layer: Ni-CF 6wt%, MXene 0.3wt%, Fe3O4@SiO2 1.2wt%, total filler 7.5wt%; loss absorption layer: Ni-CF 10wt%, MXene 0.5wt%, Fe3O4@SiO2 2.0wt%, total filler 12.5wt%; reflective underlayer: Ni-CF 14wt%, MXene 0.7wt%, Fe3O4@SiO2 2.8wt%, total filler 17.5wt%, and other process parameters are the same as in Example 1.
[0063] According to the formula described in Table 1, the preparation method of Example 6 is basically the same as that of Example 1, except that the electroless nickel plating time is controlled to be 5 min to obtain a thin nickel-plated carbon fiber with a nickel layer thickness of 0.5 μm. The other process parameters are the same as those in Example 1.
[0064] According to the formula described in Table 1, the preparation method of Example 7 is basically the same as that of Example 1, except that the electroless nickel plating time is controlled to be 50 min, resulting in a thick nickel-plated carbon fiber with a nickel layer thickness of 5.0 μm. The remaining process parameters are the same as in Example 1.
[0065] According to the formula described in Table 1, the preparation method of Example 8 is basically the same as that of Example 1, except that in the preparation of Fe3O4@SiO2 particles, the SiO2 coating reaction temperature is controlled at 60 ℃ and the reaction time is 4 h, and small core-shell particles with a core-shell size of 50 nm and a SiO2 shell thickness of 10 nm are prepared. The other process parameters are the same as those in Example 1.
[0066] According to the formula described in Table 1, the preparation method of Example 9 is basically the same as that of Example 1, except that in the preparation of Fe3O4@SiO2 particles, the SiO2 coating reaction temperature is controlled at 120 ℃ and the reaction time is 12 h to prepare large-sized core-shell particles with a core-shell size of 500 nm and a SiO2 shell thickness of 100 nm. The other process parameters are the same as those in Example 1.
[0067] According to the formulation described in Table 1, the preparation method of Example 10 is basically the same as that of Example 1, except that: MXene nanosheets C with a sheet size of 10 μm are used for electrostatic self-assembly, and the electrostatic self-assembly conditions are the same as those in Example 1.
[0068] According to the formulation described in Table 1, the preparation method of Example 11 is basically the same as that of Example 1, except that: MXene nanosheets C with a sheet size of 1 μm are used for electrostatic self-assembly, and the electrostatic self-assembly conditions are the same as those in Example 1.
[0069] According to the formulation described in Table 1, the preparation method of Example 12 is basically the same as that of Example 1, except that the matrix resin is changed to polyimide A2, the curing temperature is adjusted to 180 ℃ (the curing temperature of polyimide is higher), the curing time is still 3h, and the other process parameters are the same as those of Example 1.
[0070] According to the formulation described in Table 1, the preparation method of Example 13 is basically the same as that of Example 1, except that the matrix resin is changed to polyetheretherketone A3, the curing temperature is adjusted to 200 ℃, the curing time is still 3h, and the other process parameters are the same as those of Example 1.
[0071] According to the formulation described in Table 1, the preparation method of Example 14 is basically the same as that of Example 1, except that: the electrostatic voltage is controlled at 10V during electrostatic self-assembly, the assembly time is 1.0h, the MXene coverage rate is about 60%, and the other process parameters are the same as those in Example 1.
[0072] According to the formulation described in Table 1, the preparation method of Example 15 is basically the same as that of Example 1, except that: the electrostatic voltage is controlled at 50V during electrostatic self-assembly, the assembly time is 4.0h, the MXene coverage rate is about 90%, and the other process parameters are the same as those of Example 1.
[0073] According to the formula described in Table 1, the preparation method of Example 16 is basically the same as that of Example 1, except that: the vacuum degree during vacuum-assisted impregnation is -0.08MPa, the impregnation time is 2h, the curing temperature is 80℃, the curing time is 2h, and the other process parameters are the same as those in Example 1.
[0074] According to the formula described in Table 1, the preparation method of Example 17 is basically the same as that of Example 1, except that: the vacuum degree during vacuum-assisted impregnation is -0.10MPa, the impregnation time is 6h, the curing temperature is 200℃, the curing time is 4h, and the other process parameters are the same as those in Example 1.
[0075] According to the formulation described in Table 1, the preparation method of Example 18 is basically the same as that of Example 1, except that the thickness of the transition interface region is 150 μm, which is achieved by controlling the gradient transition distance of the interlayer filler. The other process parameters are the same as those in Example 1.
[0076] According to the formulations described in Table 1, Comparative Example 1 is a single-layer uniform composite material without a gradient structure. Nickel-plated carbon fiber-MXene composite filler and Fe3O4@SiO2 particles D are uniformly dispersed in epoxy resin A1 matrix at a total filler content of 25wt% (the same as the total filler content of the loss absorption layer in Example 1). The impedance matching layer, loss absorption layer and reflection underlayer are not distinguished. Ordinary compression molding process is used instead of vacuum-assisted impregnation molding. The curing conditions are 150 degC / 3h, and a single-layer uniform structure composite material with a thickness of 3mm is prepared.
[0077] According to the formulation described in Table 1, Comparative Example 2 is a composite material without MXene nanosheets. The preparation method is basically the same as that of Example 1, except that the electrostatic self-assembly step is omitted, MXene nanosheets C are not added, only nickel-plated carbon fiber B is used as a conductive filler, the thickness ratio of the three layers is still 3:4:2, and the contents of Ni-CF and Fe3O4@SiO2 in each layer are adjusted accordingly so that the total filler content of each layer is consistent with the corresponding layer in Example 1.
[0078] According to the formulation described in Table 1, Comparative Example 3 is a composite material without Fe3O4@SiO2 particles. The preparation method is basically the same as that of Example 1, except that the Fe3O4@SiO2 particle preparation step is omitted, Fe3O4@SiO2 particles D are not added, the thickness ratio of the three layers is still 3:4:2, and the Ni-CF and MXene contents of each layer are adjusted accordingly to keep the total filler content of each layer consistent with the corresponding layer of Example 1.
[0079] According to the formulation described in Table 1, Comparative Example 4 is a composite material without nickel-plated carbon fiber. The preparation method is basically the same as that of Example 1, except that: the chemical nickel plating step is omitted, nickel-plated carbon fiber B and MXene nanosheets C are not added (because MXene is coated on the surface of Ni-CF through electrostatic self-assembly), and only Fe3O4@SiO2 particles D are used as functional fillers. The thickness ratio of the three layers is still 3:4:2, and the Fe3O4@SiO2 content of each layer is adjusted accordingly.
[0080] The following tests were performed on the composite material. Unless otherwise specified, all tests were conducted at 25°C. The main indicators are as follows: 1. Bending strength (MPa): Tested according to GB / T 1447-2005, with a sample span-to-thickness ratio of 16:1 and a loading rate of 2 mm / min; 2. Interlaminar shear strength (MPa): Tested according to GB / T 1450.1-2005, with a sample span of 10 mm and a loading rate of 1 mm / min; 3. Electromagnetic shielding effectiveness (dB): Tested according to ASTM D4935-10, the sample is annular: outer diameter 133mm, inner diameter 6.35mm, and the test band range is 8.2-18GHz; 4. Surface reflectance (dB): Tested according to ASTM D4935-10. The sample is annular: outer diameter 133mm, inner diameter 6.35mm, and the test band range is 8.2-18GHz. The smaller the surface reflectance, the less reflection and the higher the absorption ratio. 5. Conductivity (S / m): Tested using the four-probe method, sample size 25mm x 25mm, DC conductivity; 6. Dielectric constant (10GHz): Tested according to IPC-TM-650, sample size 50mm x 50mm, thickness measured.
[0081] 7. Absorption rate: Tested according to ASTM D4935-10. The sample is annular: outer diameter 133mm, inner diameter 6.35mm, test band range 8.2-18GHz, absorption rate = 1-RT, R is reflectivity, and T is transmittance.
[0082] Table 2: Table 2 shows that there were a total of 22 test schemes in 18 examples and 4 comparative examples. Examples 1-11 used epoxy resin A1 as the matrix and investigated the influence of each factor on the electromagnetic shielding performance of the composite material by changing a single parameter in the system. Examples 12-13 verified the applicability of polyimide and polyetheretherketone matrix respectively. Examples 14-17 covered the upper and lower limits of electrostatic assembly, vacuum impregnation and curing process parameters respectively. Example 18 verified the upper limit of the thickness of the transition interface region. Comparative examples 1-4 proved from the opposite perspective the necessity and synergistic effect of gradient structure and three functional fillers in the technical solution of this example. At the same time, the beneficial effect of dispersion distribution has been verified by comparative experiments: the sample prepared according to the method of this example (Example 1) has an electromagnetic shielding effectiveness of 78dB and an absorption rate of 82% in the 8.2-18GHz frequency band; the comparative example 1, which uses the same formula but is prepared by simple mechanical stirring and mixing (embedding method), has an electromagnetic shielding effectiveness of only 52dB and an absorption rate of 45%, proving that dispersion distribution plays a key role in improving electromagnetic shielding performance. Experimental data show that, under the same total filler content (5wt%), the electromagnetic shielding effectiveness of the dispersed distribution method is 8-15dB higher than that of the embedded method, and the absorption rate is 12-20% higher. In addition, the comparison between Example 1 and Comparative Example 1 also verifies the key role of the transition interface region: Example 1 formed a transition interface region with a thickness of about 80μm through concentration difference diffusion during layered laying and vacuum impregnation process, which significantly reduced the reflection of electromagnetic waves at the interlayer interface, with a surface reflection coefficient of -4.2dB; while Comparative Example 1 is a single-layer uniform structure without a transition interface region, and its surface reflection coefficient is -12.5dB, indicating that the transition interface region effectively reduces surface reflection and increases the absorption ratio.
[0083] The above embodiments are only for illustrating the technical concept and features of the present invention, and are intended to enable those skilled in the art to understand the content of the present invention and implement it accordingly. They should not be construed as limiting the scope of protection of the present invention. All equivalent changes or modifications made in accordance with the spirit and essence of the present invention should be covered within the scope of protection of the present invention.
Claims
1. A carbon fiber electromagnetic shielding composite material, characterized in that: It includes an impedance matching layer, a loss absorption layer, and a reflective underlayer, which are sequentially distributed along the thickness direction. A transition interface region is provided between the impedance matching layer and the loss absorption layer, and between the loss absorption layer and the reflective underlayer. The impedance matching layer, loss absorption layer, and reflective underlayer all contain a matrix material and functional fillers distributed within the matrix material. The functional fillers include nickel-plated carbon fibers, MXene nanosheets, and Fe3O4@SiO2 particles. The MXene nanosheets coat the surface of the nickel-plated carbon fibers and form a conductive framework that penetrates the impedance matching layer, loss absorption layer, and reflective underlayer. The Fe3O4@SiO2 particles are dispersed in the three-dimensional network gaps of the conductive framework. The total content of functional fillers in the loss absorption layer is higher than that in the impedance matching layer, and the content of nickel-plated carbon fibers in the reflective underlayer is higher than that in the loss absorption layer.
2. The carbon fiber electromagnetic shielding composite material according to claim 1, characterized in that: The total content of the functional filler is 7.5~47wt%, of which: the content of the nickel-plated carbon fiber is 16~32wt%, the content of the MXene nanosheets is 0.3~6wt%, and the content of the Fe3O4@SiO2 particles is 1.2~9wt%.
3. The carbon fiber electromagnetic shielding composite material according to claim 1 or 2, characterized in that: In the impedance matching layer: the total content of the functional filler is 7.5~25wt%, of which: the content of the nickel-plated carbon fiber is 6~18wt%, the content of the MXene nanosheets is 0.3~2wt%, and the content of the Fe3O4@SiO2 particles is 1.2~5wt%; In the loss absorption layer: the total content of the functional filler is 12.5~38wt%, of which: the content of the nickel-plated carbon fiber is 10~25wt%, the content of the MXene nanosheets is 0.5~5wt%, and the content of the Fe3O4@SiO2 particles is 2~5wt%; In the reflective substrate: the total content of the functional filler is 17.5~47wt%, of which: the content of the nickel-plated carbon fiber is 14~32wt%, the content of the MXene nanosheets is 0.7~6wt%, and the content of the Fe3O4@SiO2 particles is 2.8~9wt%.
4. The carbon fiber electromagnetic shielding composite material according to claim 1, characterized in that: The total thickness of the composite material is 1~5mm, the thickness ratio of the impedance matching layer, the loss absorption layer and the reflective underlayer is (2~4):(3~6):(1~3), and the thickness of the transition interface region is 30~150μm.
5. The carbon fiber electromagnetic shielding composite material according to claim 1, characterized in that: The composite material, from the impedance matching layer to the reflective substrate, has a gradually increasing dielectric constant, a gradually increasing magnetic permeability, and a gradually increasing electrical conductivity.
6. The carbon fiber electromagnetic shielding composite material according to claim 1 or 5, characterized in that: The impedance matching layer has a relative permittivity of 5 to 20 and a permeability close to 1; the loss absorption layer has a relative permittivity of 10 to 35 and a permeability of 1.5 to 6; the reflective substrate has a conductivity greater than 50 S / m.
7. The carbon fiber electromagnetic shielding composite material according to claim 1, characterized in that: The matrix material is selected from one or more of epoxy resin, polyimide, polyetheretherketone, polyphenylene sulfide, unsaturated polyester, phenolic resin and their modifiers.
8. The carbon fiber electromagnetic shielding composite material according to claim 1, characterized in that: The composite material has an electromagnetic shielding effectiveness of 65-85dB in the 8.2-40GHz frequency band, an electromagnetic wave absorption rate of more than 80%, and a surface reflection coefficient of less than 5dB.
9. A method for preparing the carbon fiber electromagnetic shielding composite material according to any one of claims 1 to 9, characterized in that: include: (1) Electroless nickel plating is performed on carbon fibers to obtain nickel-plated carbon fibers. (2) MXene nanosheets were electrostatically self-assembled onto the surface of nickel-plated carbon fiber to obtain nickel-plated carbon fiber-MXene composite filler. (3) Fe3O4@SiO2 particles were obtained by coating the surface of Fe3O4 with a SiO2 shell using an in-situ grafting method. (4) Nickel-plated carbon fiber-MXene composite filler and Fe3O4@SiO2 particles are combined with matrix material in a gradient ratio to prepare an impedance matching layer, a loss absorption layer and a reflective underlayer. In each layer, nickel-plated carbon fiber-MXene composite filler forms a conductive skeleton and Fe3O4@SiO2 particles are dispersed in the three-dimensional network gaps of the conductive skeleton. The impedance matching layer, loss absorption layer and reflective underlayer are laid in sequence. There is a preset filler concentration difference between adjacent layers of slurry. This concentration difference drives the filler to permeate and diffuse at the interlayer contact interface. Through vacuum-assisted impregnation, the resin matrix flows and drives Fe3O4@SiO2 to redistribute between layers. At the same time, the vacuum pressure makes each layer fit tightly but does not eliminate the established concentration gradient. After curing and shaping, the resin matrix gels and locks the formed concentration gradient into a stable transition interface region, and the composite material is obtained.
10. The preparation method according to claim 9, characterized in that: The length of the nickel-plated carbon fiber is 1-10 mm, and the thickness of the nickel plating layer in the electroless nickel plating is 0.5-5 μm. The MXene nanosheets have a length of 1-10 μm, are Ti3C2Tx, and have a coating rate of 60-90% on the nickel-plated carbon fiber surface. The core-shell length of Fe3O4 in the Fe3O4@SiO2 particles is 50-500 nm, and the thickness of the SiO2 shell is 10-100 nm.
Citation Information
Patent Citations
Modified carbon fiber electromagnetic shielding composite material
CN117801465A
High-performance broadband electromagnetic shielding carbon fiber prepreg
CN120248529A
Nickel plating carbon fiber plate with electromagnetic shielding performance
CN205223076U
